AGARICOMYCETES MEDICINAL MUSHROOMS WITH POTENTIAL NEUROPROTECTIVE ACTIVITY GROWING IN ARMENIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The Agaricomycetes mushrooms (phylum Basidiomycota) are recognised sources of valuable food and medicines. They are producers of bioactive compounds (phenolics, polysaccharides, proteins, steroids, terpenoids, etc.) possessing around 130 therapeutic effects (antimicrobial, anti-inflammatory, antioxidant, immunomodulatory, etc.). Mushrooms are also reported as potential neurotrophic and neuroprotective agents. Seventeen edible and inedible agaricomycetous species from different taxonomic and ecological groups have been reported in Armenia to possess neuroprotective activity. Evaluation resource value and biotechnological potential of Armenian agaricomycetous mushrooms will assist further development of novel myco-pharmaceuticals to prevent and mitigate different disorders, including neurodegenerative.
Keywords: agaricomycetes; antioxidant; anti-inflammatory; mushrooms; neurodegenerative; neuroprotective